METHODOLOGY AND CHARACTERISTICS OF DETERMINING THE ACTIVITY RATING OF BANKS IN FOREIGN COUNTRIES. (World Economics and Finance Bulletin, 2022)
The analysis of the modern banking system and the activity of commercial banks also require methodological support and the study of advanced foreign experiences in rating the activity of commercial banks. There are different methodologies for determining the rating of commercial banks, and it was found that they differ from each other depending on the characteristics of countries and rating companies.. There are different aspects and specific features of the methodologies for determining the rating of commercial banks. This article illustrates that the methodology and features of rating evaluation of banks in developed foreign countries
Keywords: Commercial bank; rating; ranking; asset quality